Temporal changes in the incidence and predictors of severe hypoglycaemia in type 2 diabetes: The Fremantle Diabetes Study. Issue 3 (25th November 2018) - Davis, Timothy M. E.; Bruce, David G.; Finn, Judith; Curtis, Bradley H.; Barraclough, Helen; Davis, Wendy A.
Abstract : Aim: To determine the incidence of severe hypoglycaemia and its predictors in community‐based patients with type 2 diabetes studied between 2008 and 2013 compared with those in a cohort of patients with type 2 diabetes from the same geographical area assessed a decade earlier. Methods: We studied 1551 participants (mean age 65.7 years, 51.9% men) with type 2 diabetes from the longitudinal observational Fremantle Diabetes Study Phase II (FDS2). Severe hypoglycaemia was ascertained as that requiring ambulance attendance, emergency department services and/or hospitalization. Cox proportional hazards modelling was used to determine predictors of a first episode of severe hypoglycaemia, and negative binomial regression was used to identify predictors of frequency. Results: Sixty‐three participants (4.1%) experienced 83 episodes, representing an incidence of 1.34/100 participant‐years (95% confidence interval [CI] 1.08 to 1.67; vs 1.67/100 participant‐years [95% CI 1.31‐2.13] in the Fremantle Diabetes Study Phase I [FDS1]; P = 0.18). Those experiencing severe hypoglycaemia experienced one to four episodes in both cohorts. The independent predictors of incident severe hypoglycaemia in the FDS2 were: older age; higher educational attainment; alcohol consumption; current smoking; sulphonylurea/insulin treatment; prior severe hypoglycaemia; renal impairment; and plasma N‐terminal pro‐B‐type natriuretic peptide (NT‐proBNP). The same variables except smoking were associated with frequency of severe hypoglycaemia. Most of these risk factors paralleled those in the FDS1, but current smoking and plasma NT‐proBNP were novel. Conclusions: The incidence and frequency of severe hypoglycaemia did not change between the Fremantle Diabetes Study phases but novel risk factors, including plasma NT‐proBNP, were observed in the FDS2.